The Potential of Anthropometry in Winning Medals in the PON Qualifying Round for Major Sports - Humaedi Humaedi; Andi Saparia; Andi Su ltan Brilin Susandi Eka Wahyudhi (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. The performance of athletes in sports is influenced by various factors such as their profile, anthropometry, training, equipment, management, nutrition, and the environment. This research aims to determine the potential impact of anthropometry on winning medals in the PON qualifying rounds for major sports. The primary goal is to understand the significance of anthropometry in achieving success in these sporting events. Materials and methods. This study utilizes a quantitative descriptive method with a survey research approach. The research focuses on 11 sports branches registered with the provincial KONI, comprising a total of 70 outstanding athletes. The variables studied and data collection techniques include height, weight, leg length, and arm length. The study findings indicated that one sports branch did not win any medals at the BK PON, while six sports branches did receive medals. Only 33 out of the 70 participating athletes managed to secure medals. Results. The athletes' performance at BK PON did not meet expectations, largely due to a range of individual factors. It became evident that meticulous planning was required for each athlete's training and competition experience. Areas requiring improvement included technical flexibility, tactical prowess, creativity in competition, as well as mental and emotional adjustments. Conclusion. The study gathered anthropometric data from seven different sports. Interestingly, one of these sports did not produce any medal winners. Even among the top six sports, athletes with ideal anthropometry were unable to secure medals. This is likely due to a combination of individual factors. It is essential to carefully plan each athlete's training and competitive experience, improve technical flexibility, tactics, and creativity in competition, as well as train for mental and emotional adjustments.